"Wild Weirdness?" "Gross Humbugs!": Memory-Images of the North and Finnish Photography - Möller, Frank (Journal of Northern Studies, 2012)
In this essay it is argued that northern photography can serve as an epistemological triangle both combining different layers of experiences and memories with one another—experience in the north, experience as inhabitants of the north and experience as such—and connecting photographers, subjects of photography and viewers with one another. The essay discusses selected photographs of northern indigenous people and landscapes—and the approaches underlying them—in terms of what is here deemed key concepts in social research including northern studies: experience and memory. Owing to the surplus of meaning that images inevitably carry with them and their irreducibility to one meaning, photographic images, it is argued, contribute to what Sherrill Grace has called the north’s “resistance to measure and closure.” Images may help the beholder to acknowledge that different groups of people may have different memories of what only seems to be the same history. A brief discussion of the work of Jorma Puranen, Tiina Itkonen and Antero Takala substantiates these claims.